Fifteen years of phishing: can technology save us?. Issue 7 (July 2019) - Furnell, Steven; Millet, Kieran; Papadaki, Maria
Abstract : With the first incidents dating back to 2003, phishing has now been a problem for over a decade and a half. Unfortunately, just like malware, it's proven to be the cyber security equivalent of an unwanted genie that we can't put back in the bottle. Despite many efforts to educate users and provide safeguards, people are still falling victim. Although it is a long-established threat, phishing continues to grow and represents a significant issue for individuals and organisations. Steven Furnell, Kieran Millet and Maria Papadaki of the Centre for Security, Communications and Network Research, University of Plymouth, UK, examine the scale of the problem and look at the effectiveness of some of our technology-based defences. And they present the results of a practical assessment of the capabilities of email services to identify and highlight phishing based upon message content.